2007
DOI: 10.1016/j.cogdev.2007.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Actors and actions: The role of agent behavior in infants’ attribution of goals

Abstract: Twelve-month-old infants attribute goals to both familiar, human agents and unfamiliar, non-human agents. They also attribute goal-directedness to both familiar actions and unfamiliar ones. Four conditions examined information 12-month-olds use to determine which actions of an unfamiliar agent are goal-directed. Infants who witnessed the agent interact contingently with a human confederate encoded the agent's actions as goal-directed; infants who saw a human confederate model an intentional stance toward the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 34 publications
2
81
0
Order By: Relevance
“…These findings receive support from several studies that investigate infants' evaluations of past events, all of which focus on the ability to encode the goal of others actions (Sommerville, Woodward, & Needham, 2005;Woodward, 1998). Unlike goal anticipation, the ability to encode the goal of observed actions is not limited to human actions (Johnson, Shimitzu, & Ok, 2007;Luo & Baillargeon, 2005;Shimizu & Johnson, 2004). However, infant's ability to encode the goal of observed events are strengthened if the observed events match ones own experiences and manual capabilities.…”
Section: Introductionmentioning
confidence: 78%
“…These findings receive support from several studies that investigate infants' evaluations of past events, all of which focus on the ability to encode the goal of others actions (Sommerville, Woodward, & Needham, 2005;Woodward, 1998). Unlike goal anticipation, the ability to encode the goal of observed actions is not limited to human actions (Johnson, Shimitzu, & Ok, 2007;Luo & Baillargeon, 2005;Shimizu & Johnson, 2004). However, infant's ability to encode the goal of observed events are strengthened if the observed events match ones own experiences and manual capabilities.…”
Section: Introductionmentioning
confidence: 78%
“…The results of Kamewari et al (2005), Johnson, Shimizu, et al (2007), and Csibra (2008) all indicated that self-propulsion or autonomous motion alone is not sufficient to lead infants to categorize a novel entity as an agent: The entity must provide evidence that it has autonomous control over its actions. These findings left open the possibility that self-propulsion, though not sufficient, is still necessary for infants to view an entity as an agent.…”
Section: Can An Agent Be Inert?mentioning
confidence: 99%
“…Ground-breaking experiments by Johnson and her colleagues (e.g., Johnson, Shimizu, & Ok, 2007;Shimizu & Johnson, 2004) helped shed light on this question. In these experiments, 12-month-olds received a two-object task in which an oval-shaped "blob" 38 covered with green fiberfill stood near the front of the apparatus; at the back of the apparatus were two toys, object-A on one side and object-B on the other.…”
Section: How Do Infants Identify Non-human Agents?mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the core-domain view (15), infants' concept of self-propulsion is part of the skeletal explanatory framework that underlies core physical reasoning: when a novel object gives evidence that it is capable of autonomous motion (e.g., begins to move on its own), infants attribute to the object an internal source of energy, and they appreciate that the object may use its energy to reverse course, resist efforts to move it, and so on (16). Similarly, infants' concept of agency is part of the skeletal explanatory framework that underlies core psychological reasoning: when a novel object provides evidence that it has autonomous control over its actions (e.g., responds contingently to events in its environment), infants attribute to the object motivational, epistemic, and other internal states, and they use these states to predict and interpret the object's actions (17). In contrast, according to the image-schema view (18), infants' concepts of selfpropulsion and agency are formed by a perceptual-meaning-analysis mechanism that redescribes spatiotemporal information into meaningful iconic representations.…”
mentioning
confidence: 99%